Ответы и объяснения

  • 04m
  • новичок
2012-11-07T18:54:51+04:00

x(x + 3)(x + 5)(x + 8) + 56 = 0
Заметим, что x(x + 8) = x² + 8x, а (x + 3)(x + 5) = x² + 8x + 15. Напрашивается замена ведь.
Переписываем уравнение так:
(x² + 8x)(x² + 8x + 15) + 56 = 0
1) Замена: x² + 8x = t
t(t + 15) + 56 = 0
t² + 15t + 56 = 0
t₁ = -8
t₂ = -7
2) x² + 8x = -8
x² + 8x + 8 = 0
D = 64 - 4*8 = 32
x₁ = (-8 + √32) / 2 = (-8 + 4√2) / 2 = (4(-2 + √2)) / 2 = -4 + √8
x₂ = -4 - √8

x² + 8x = -7
x² + 8x + 7 = 0
x₁ = -7
x₂ = 1

Ответ:
x₁ = -4 + √8
x₂ = -4 - √8
x₃ = -7
x₄ = 1